The Influence of Cu2+ Salts on the Enzymatic Activity of Aspergillus niger Clinical Isolates - A.A. Bayazitova; E.V. Khaldeeva; N.I. Glushko; S.A. Lisovskaya; V.R. Parshakov; O.N. Ilinskaya (Учёные записки Казанского университета: Серия Естественные науки)
The influence of heavy metals on the enzymatic activity of Aspergillus niger is analyzed. The effects of Cu2+ on the growth rate, antimycotic resistance, as well as amylolytic and lipolytic activity of various clinical isolates of Aspergillus niger are studied. The obtained results show that Cu2+ reduces the growth rate and sporogenesis of the clinical isolates of Aspergillus niger. Partial inhibition of the lipolytic activity by the high concentrations of Cu2+ salts is found. Addition of Cu2+ salts to the medium affects the susceptibility of the clinical isolates of Aspergillus niger to antimycotic drugs. The dependence of the susceptibility of micromycetes to antimycotic drugs on the concentration of Cu2+ is emphasized.